ChemInform Abstract: Base‐Free, One‐Pot Chemocatalytic Conversion of Glycerol to Methyl Lactate Using Supported Gold Catalysts. Issue 36 (9th September 2014) - Purushothaman, Rajeesh Kumar P.; van Haveren, Jacco; Melian‐Cabrera, Ignacio; van Eck, Ernst R. H.; Heeres, Hero J.
Abstract Au nanoparticles on ultra‐stable zeolite‐Y catalyzes the reaction of glycerol to methyl lactate in methanol.